Geography, institutions, and the making of comparative development - Raphael A. Auer (Center for Economic Studies and ifo Institute (CESifo), 2012)
While the direct impact of geographic endowments on prosperity is present in all countries, in former colonies, geography has also affected colonization policies and, therefore, institutional outcomes. Using non-colonized countries as a control group, I re-examine the theories put forward by La Porta et al. (1999) and by Acemoglu et al. (2001), finding strong support for both theories, but also evidence that the authors' estimates are mildly biased since they confound the effect of the historical determinants of institutions with the sizeable direct impact of geographic endowments on development.
Keywords: O11; P16; P51; R11; N50; F54; 330; growth; institutions; geography; comparative development; colonialism; Wirtschaftswachstum; Entwicklung; Institutionalismus; Wirtschaftsgeographie; Kolonialismus; Vergleich; Welt